1989
DOI: 10.1002/ana.410250315
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical investigation of the human neostriatum in huntington's disease

Abstract: The neostriatum of 7 autopsied patients with Huntington's disease (HD) was examined immunohistochemically using purified antibody against calcineurin, which may be present only in the medium-size spinous neurons of the mammalian striatum. This study revealed a marked loss of calcineurin-positive cells in the caudate nucleus and the putamen in all HD patients, compared with control subjects, and there was some variation among the HD patients. Four HD patients showed significantly lower density of calcineurin-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 32 publications
3
42
0
Order By: Relevance
“…The observed reduction in huntingtin phosphorylation could result from a reduction in Akt activity (Colin et al, 2005) but also from an excess of calcineurin phosphatase activity. Indeed, calcineurin phosphatase is highly expressed in the striatum and in particular in the medium-size spiny neurons (MSNs), the first cells to degenerate in HD (Goto et al, 1989), and could therefore predispose huntingtin to dephosphorylation in these cells. Calcineurin is activated by Ca 2ϩ (Mansuy, 2003), and several studies indicate that excessive Ca 2ϩ entry in striatal neurons could play a role in HD (Bezprozvanny and Hayden, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The observed reduction in huntingtin phosphorylation could result from a reduction in Akt activity (Colin et al, 2005) but also from an excess of calcineurin phosphatase activity. Indeed, calcineurin phosphatase is highly expressed in the striatum and in particular in the medium-size spiny neurons (MSNs), the first cells to degenerate in HD (Goto et al, 1989), and could therefore predispose huntingtin to dephosphorylation in these cells. Calcineurin is activated by Ca 2ϩ (Mansuy, 2003), and several studies indicate that excessive Ca 2ϩ entry in striatal neurons could play a role in HD (Bezprozvanny and Hayden, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Medium-sized spiny striatal neurons, and those neurochemical substances contained within them, are disproportionately affected early and most severely in HD (Marshall et al, 1983;Graveland et al, 1985;Ferrante et al, 1986Ferrante et al, , 1991Seto-Oshima et al, 1988;Goto et al, 1989), whereas large and medium-sized aspiny striatal neurons and their chemical components are relatively spared (Dawbarn et al, 1985;Ferrante et al, , 1987aAlbin et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Excitotoxic processes preferentially affecting one EAA receptor subtype would give rise to discrete striatal pathology. The phenomenon of compartment-specific abnormalities has been postulated to contribute to the pathophysiology of Huntington disease (80)(81)(82). It has been demonstrated that enkephalinergic striatal projections to the GPe are affected early in the disease (61).…”
Section: Discussionmentioning
confidence: 99%